Odradzanie się harcerstwa polskiego po 1956 r. i próby włączenia go w struktury systemu wychowawczego szkoły - Grzybowski, Romuald (Biuletyn Historii Wychowania, 2007)
The Polish scouting movement, which wrote such a beautiful page of history during  the Second World War, after 1945 found itself in an extremely difficult situation. The aims and the forms of educational influence of ZHP (poi. abbr. Związek Harcerstwa Polskiego - Polish Scouting Association) proved unacceptable by the government of a totalitarian state, which the Polish People’s Republic (Polska Rzeczpospolita Ludowa - PRL) was. As a result, ZHP was originally marginalized, and then, for several years, had been completely dissolved. The reconstruction of the scouting movement started at the end of 1956, on the wave of a political thaw. Such actions led, in the years 1956-1958, to a formal recreation of ZHP, however, since then, this organization was entirely subject to PZPR (Polish communist party). Consequently, following 1958, ZHP was incorporated into the structure of a communist youth movement in Poland. Moreover, in accordance with the rules of the socialist political system and the principles of a planned economy, the scouting movement was „delegated” to work in school. Since then, in compliance with the guidelines of the Central Committee of PZPR, the activity of the Polish Scouting Association (ZHP) was to become an integral element of the school's educational programme. It meant that the scouting movement was supposed to actively participate in shaping of socialist attitudes in children and youth, according to the main task of the Polish school which was reformed in 1961. Unexpectedly, the party authorities and educational authorities were confronted with the opposition of ZHP leadership that they controlled. ZHP, for a long time, resolutely rejected the suggestion about a necessity to strengthen the ties of this organization and school. In reality, in early 1960s, the scouting movement defended the remnants of its autonomy, struggling against becoming one of the tools for shaping a young generation of Poles through ideologized Polish school. The practice showed that the arguments of scouts did not have any significance for communist authorities as they consequently kept on achieving their own goals.